Klf2 Is an Essential Factor that Sustains Ground State Pluripotency - Yeo, Jia-Chi (2016)
The maintenance of mouse embryonic stem cells (mESCs) requires LIF and serum. However, a pluripotent “ground state,” bearing resemblance to preimplantation mouse epiblasts, can be established through dual inhibition (2i) of both prodifferentiation Mek/Erk and Gsk3/Tcf3 pathways. While Gsk3 inhibition has been attributed to the transcriptional derepression of Esrrb, the molecular mechanism mediated by Mek inhibition remains unclear. In this study, we show that Krüppel-like factor 2 (Klf2) is phosphorylated by Erk2 and that phospho-Klf2 is proteosomally degraded. Mek inhibition hence prevents Klf2 protein phosphodegradation to sustain pluripotency. Indeed, while Klf2-null mESCs can survive under LIF/Serum, they are not viable under 2i, demonstrating that Klf2 is essential for ground state pluripotency. Importantly, we also show that ectopic Klf2 expression can replace Mek inhibition in mESCs, allowing the culture of Klf2-null mESCs under Gsk3 inhibition alone. Collectively, our study defines the Mek/Erk/Klf2 axis that cooperates with the Gsk3/Tcf3/Esrrb pathway in mediating ground state pluripotency.